1995
DOI: 10.1149/1.2048672
|View full text |Cite
|
Sign up to set email alerts
|

NiO Dissolution in Molten Carbonate Fuel Cells: Effect on Performance and Life

Abstract: The short-circuit phenomenon caused by dissolution of the NiO cathode in the molten carbonate fuel cell was experimentally investigated. Monitoring CQ concentration in the anode exhaust gas can be an effective way to detect cell short circuit. The effects of matrix thickness and cathode CQ partial pressure on shorting were elucidated. The time-to-initialshort-circuit (shorting time) is approximately proportional to the second power of the matrix thickness and the reciprocal of the cathode CO2 partial pressure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…[2], [3] and [4] as follows: The value of  c evaluated from Allen-Hickling plots was 0.34, the a and b of reaction order in the eqs. [4] and [5] were 0.31 0.08 and -0.35  0.04, respectively. So the reaction on LaNiO 3 for the ORR might be competed mechanism of POP and PCP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2], [3] and [4] as follows: The value of  c evaluated from Allen-Hickling plots was 0.34, the a and b of reaction order in the eqs. [4] and [5] were 0.31 0.08 and -0.35  0.04, respectively. So the reaction on LaNiO 3 for the ORR might be competed mechanism of POP and PCP.…”
Section: Resultsmentioning
confidence: 99%
“…The MCFC system can use various fuels without precious metal, and has higher energy conversion efficiency compared with room temperature fuel cells such as polymer electrolyte fuel cell (PEFC) systems (3). Pressurized MCFC system has higher efficiency than ambient pressure one, but it has a serious problem in lifetime caused by dissolution of NiO cathode into the electrolyte and the internal short-circuit of Ni (Ni shorting) (4).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon should therefore be avoided during the regular lifetime of the cells. CRIEPI has tested many cells under various pressure conditions with various cell specifications and found that the time to start short-circuiting is mainly determined by the cathode CO 2 partial pressure and the matrix thickness [17]. The relationship is expressed as follows:…”
Section: Life Time Estimationmentioning
confidence: 99%
“…Reduced nickel particles form internal short-circuiting bridges within the electrolyte matrix. Since the shorting time relates to the partial pressure of carbon dioxide at the cathode side, based on CRIEPI's experiments (8), it could be traded off subject to setting the operation pressure which affects cell voltage directly. Electrolyte loss is caused mainly by corrosion, as well as by creepage and vaporization.…”
Section: Mcfc Longer Life and Lower Cost Technologiesmentioning
confidence: 99%